SARM1 deletion inhibits astrogliosis and BBB damage through Jagged-1/Notch-1/NF-κB signaling to improve neurological function after ischemic stroke - Yan Qiong Fu; Yu Zheng; Zhuo Li Li; Xin Yi Huang; Xiao Wan Wang; Mai Yin Cui; Yun Qi Zhang; Bing Rui Gao; Chan Zhang; Xiao Xiao Fan; Yong Jian; Bai Hui Chen (Neurobiology of Disease)
Reactive astrogliosis is a critical process in the development of ischemic stroke. However, the precise mechanism by which reactive astrogliosis changes the pathogenesis of ischemic stroke remains elusive. Sterile alpha and TIR motif-containing 1 protein (SARM1) plays a key role in axonal degeneration and is involved in different cell death programs that regulate neuronal survival. The present study investigated the role of SARM1 in regulating reactive astrogliosis and neurological function after stroke in whole-body SARM1 knockout (SARM1−/−) mice. SARM1−/− mice showed significantly smaller infarction, slighter apoptosis, and fewer neurological function deficits 1–7 days after ischemic injury. Immunohistochemistry, western blot, and real-time PCR analyses revealed that compared with the wild-type (WT) mice, SARM1−/− mice exhibited reduced astrocytic proliferation, increased anti-inflammatory astrocytes, decreased glial scar formation in the infarct zone on day 7 after ischemic injury. SARM1 deletion also suppressed cerebral microvascular damage and blood-brain barrier (BBB) injury in ischemic brains. Mechanistically, SARM1 deletion inhibited the stroke-triggered activation of NF-κB signaling and decreased the expression of Jagged-1 and NICD in astrocytes. Overall, these findings provide the first line of evidence for a causative role of SARM1 protein in ischemia-induced reactive astrogliosis and ischemic neurovascular damage.